Epistemology of Islam Nusantara: Transformation of Islamic Legal Thought in Nahdlatul Ulama (NU) - Luthfi Hadi Aminuddin; Isnatin Ulfah (Faculty of Sharia UIN Kiai Ageng Muhammad Besari Ponorogo, 2021)
The term Islam Nusantara has created pros and cons among Islamic leaders in Indonesia. For Nahdlatul Ulama (NU), Islam Nusantara is not a new teaching or sect in Islam, so there is no need to worry. Meanwhile, other groups think that the term Islam Nusantara will reduce the universality of Islam. Therefore, this study focuses on NU’s concept of Islam Nusantara and its application and epistemological construction of Islam Nusantara. This study found that Islam Nusantara is Islam practiced in Indonesia with the epistemological basis of maqÄÅŸid al-sharÄ«a, manhaj al-fikr ahl al-sunnah wa al-jamÄ’ah, and al-”˜urf. The epistemological foundation resulted in the typical ijtihad of Islam Nusantara. In the field of constitutional law, the results of the ijtihad Islam Nusantara gave birth to the concept that Indonesia is a peaceful country (dÄr al-ÅŸulá¸¥ or dÄr al-salÄm). Meanwhile, in social, cultural, and religious realms, the epistemology of Islam Nusantara gave birth to the tradition of halal bi halal and tahlilan. In the circumstances of fiqh, there are several results of ijtihad, such as imsÄk (holding all things that may be breakfast 10 minutes before Shubuh prayer).